2013
DOI: 10.1248/bpb.b13-00645
|View full text |Cite
|
Sign up to set email alerts
|

Neuropharmacologic Studies on the Brain Serotonin<sub>1A</sub> Receptor Using the Selective Agonist Osemozotan

Abstract: Alterations in serotonin (5-HT) neurochemistry have been implicated in the etiology of major neuropsychiatric disorders such as anxiety-spectrum disorders, depression, and schizophrenia. The neuromodulatory effects of 5-HT are mediated through 14 receptor subtypes, and those receptors, including the 5-HT 1A receptor, are considered to be potential targets for the treatment of psychiatric disorders. We developed the novel 5-HT 1A receptor agonist MKC-242 (called osemozotan) and characterized its neurochemical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 145 publications
(127 reference statements)
0
11
0
1
Order By: Relevance
“…Isolation rearing-induced aggression has been proposed to be useful as an animal model for assessing benzodiazepine and non-benzodiazepine anxiolytic activities. We have found that the selective 5-HT 1A receptor agonist osemozotan (previously called as MKC-242) (3,15) as well as the g-aminobutyric acid A (GABA A )-receptor agonist diazepam reduced isolation-induced aggressive behavior (16,17). The antiaggressive effect of osemozotan was observed at low doses, suggesting the involvement of presynaptic 5-HT 1A receptor activation (6).…”
Section: Aggressive Behaviorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Isolation rearing-induced aggression has been proposed to be useful as an animal model for assessing benzodiazepine and non-benzodiazepine anxiolytic activities. We have found that the selective 5-HT 1A receptor agonist osemozotan (previously called as MKC-242) (3,15) as well as the g-aminobutyric acid A (GABA A )-receptor agonist diazepam reduced isolation-induced aggressive behavior (16,17). The antiaggressive effect of osemozotan was observed at low doses, suggesting the involvement of presynaptic 5-HT 1A receptor activation (6).…”
Section: Aggressive Behaviorsmentioning
confidence: 99%
“…The serotonin (5-HT) 1A receptor, a metabotropic G protein-coupled receptor linked to the G i/o signaling pathway, plays a crucial role in the brain development (1) and has been implicated in the etiology and treatment of schizophrenia, depression, anxiety, and pain (2,3). Positron emission tomography studies also show the altered 5-HT 1A receptor binding in patients with major depression and panic disorder (4,5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The immunoinhibitory 5-HTergic system is closely linked to other neurotransmitter systems including the dopamine (DA) ergic system [43] [46], which has been found to exert the stimulating influence on immunity [12] [30] [44] [47]- [49]. Moreover, a number of studies indicate that activation of presynaptic 5-HT 1A receptors having the effect of inhibitory regulation on the release of 5-HT, may stimulate the release of DA in several corticolimbic areas [4] [46].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a number of studies indicate that activation of presynaptic 5-HT 1A receptors having the effect of inhibitory regulation on the release of 5-HT, may stimulate the release of DA in several corticolimbic areas [4] [46]. These brain structures are also considered to play a role in immunostimulation [12] [30] [47]- [49].…”
Section: Discussionmentioning
confidence: 99%